Dampak Teori Organisasi Sistem dan Kontingensi Terhadap Sistem Manajemen dan Kepemimpinan - Fradito, Aditia; Ferunika, Ferunika; Subandi, Subandi; Makbuloh, Deden; Syarifudin, Encep (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The System Organization Theory emphasizes the importance of interactions between interdependent organizational elements to achieve common goals. Each component, such as human resources, technology, and work processes, must work synergistically to create organizational effectiveness. Meanwhile, the Contingency Theory highlights the need for strategy adjustments based on dynamic and complex environmental conditions, such as market changes and technological developments. This study aims to explore the impact of the System Organization Theory and Contingency on the management and leadership systems in organizations. The descriptive-analytical literature study method is used in the study. This study examines various theories, concepts, and previous findings related to the application of the System Organization Theory and Contingency. The results of the study indicate that the application of the System Organization Theory and Contingency can improve organizational effectiveness by creating a flexible, responsive, and adaptive structure. The application of the System Organization Theory and Contingency in Islamic education management strengthens the integration of spiritual and managerial values, creating a holistic educational model that is relevant to modern challenges. This study recommends the adoption of the System Organization Theory and Contingency as a strategic managerial approach to improve organizational performance and sustainability.